Self-Reported Perspectives from Participants in a Middle/High School Virtual Mentoring Program for Students of Color - Hintz, Haley; Freeman, Maggie; Bundy, Myra Beth; Botts, Theresa; James, Rhoman (MultiTech Publisher, 2024)
Community mentorship demonstrates benefits for adolescents of color at risk for increased life challenges. This research investigated participant-reported gains from an online mentoring program for male secondary school students initiated by Black male public school staff members. Researchers hypothesized (1) group members’ perceived confidence regarding life skills would increase, (2) qualitative responses would demonstrate increased self-efficacy regarding topics discussed in session, and (3) participants would be able to identify solutions to challenges faced by boys and men of color. Qualitative data provided some support for these hypotheses. Students detailed learned lessons and identified solutions to problems faced by members of their communities.